The Effectiveness Of Using Text Messages Reminder On Adherence With Tuberculosis Patients: A Systematic Review - Ardila Lailatul Barik; Retno Indarwati; Sulistiawati Sulistiawati (Universitas STRADA Indonesia, 2020)
Non-adherence is a factor that inhibits the completion of TB cases globally. Some studies suggest that the use of digital technology in the form of text message reminders can reduce the risk of non-adherence. The purpose of writing this article is to analyze the effectiveness of text message reminders on adherence to tuberculosis (TB) patients. The method in preparing this Systematic review is based on literature studies from various electronic databases, including Scopus, ScienceDirect, ProQuest, and Sage by conducting a comprehensive review using the PRISMA guidelines. The keywords used are